Situation Report: Romania, 15 December 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Final Text of Law on Planning Published Czechoslovak Foreign Minister Chnoupek's Visit to Romania Ceausescu to West Germany in 1973? Ceausescu to Visit Argentina More Attractive Offers to Partners in Joint Ventures? Party Authority over Culture Reinforced Personnel Changes Affecting the Council of Ministers